Alien species in aquatic environments: a selective comparison of coastal and inland waters in tropical and temperate latitudes. Issue 5 (October 2016) - Tricarico, Elena; Junqueira, Andrea O. R.; Dudgeon, David
Abstract: Biological invasions have had severe impacts on ecosystems globally, particularly affecting freshwater habitats. In the aquatic realm, marine environments have received less attention from researchers than their freshwater counterparts, and comparisons of the relative susceptibility of coastal and inland waters to alien species and their consequential impacts are lacking. The main aim of this review is to assess the 'knowns and unknowns' for alien species in aquatic habitats, evaluating the possible differences and similarities in biological invasions between freshwater and marine (coastal) environments. Three study areas with different climates and histories of bioinvasion were selected for comparison: temperate Europe, tropical Asian Hong Kong, and Neotropical Brazil. Although there were differences in spatial scale and availability of data for the three areas, fresh waters seemed to be more susceptible to invasion ‐ and experienced more impacts ‐ than coastal habitats, at least in Hong Kong and partly in Europe. Despite information about alien species in aquatic environments having increased in recent years, regional inventories remain incomplete, especially in the tropics where rigorous studies of the impacts of invasive species are generally lacking. More systematic effort is needed to develop up‐to‐date national and regional inventories of invaders, especially in the seas and particularly in the more biodiverse tropics, where the conservation gains from preventing alien invasions could be substantially greater than in other regions. Greater efforts are also required to increase public awareness of the need to prevent the establishment of potentially invasive species. Copyright © 2016 John Wiley & Sons, Ltd.